PENGARUH PENGGUNAAN ABU SEKAM PADI SEBAGAI BAHAN PENGGANTI ABU BATU DALAM CAMPURAN ASPHALT CONCRETE – WEARING COURSE (AC-WC) TERHADAP PARAMETER MARSHALL - Resy Victoria; Ade Nurdin; M.Nuklirullah (Universitas Bengkulu, 2023)
Asphalt Concrete Wearing Course (AC-WC) is the topmost layer or also known as the wear layer on the pavement which must be designed to be water-resistant, weather-resistant, and strong enough to withstand the weight of the vehicle's wheels. The AC-WC mixture consists of constituent materials, namely coarse aggregate, fine aggregate and filler. In this study, rice husk ash was used as a substitute for stone dust in the AC-WC mixture with variations in the rice husk ash mixture, namely 5%, 10%, 15%, 50%, 75% and 100%. This study aims to determine how much influence and comparison of the use of rice husk ash as a substitute for stone dust in the mixture (AC-WC) on Marshall parameters. The test was carried out with guidelines on the 2018 bina marga specification. From the results of tests carried out in the laboratory, the values ​​of the marshall parameters were obtained, namely: rice husk ash could not increase the flow value, the stability value and the marshall quotient (MQ) increased with the use of rice husk ash in variation of 5%, the variation of 10% and 15% can not meet the VIM value. Variations 50%, 75% and 100% can not be tested marshall.